Domestication of Sapium sebiferum under Jammu Conditions - Singh, Kuldeep; Kapur, S. K.; Sarin, Y. K. (Indian Forester, 1993)
Sapium sebiferum Roxb., an exotic source of oil seeds has now completely naturalized in Himalayan area. Domestication trials of this plant were carried out through seeds and root suckers under two distinct habitats. Propagation occurred fairly well through seeds and root suckers. Overall performance of the plants was comparatively better under waterlogged conditions.